PENGARUH SOCIAL CAPITAL DAN INTELECTUAL CAPITAL TERHADAP FIRM PERFORMANCE - Worokinasih, Saparila; Fuaida, Roudhotul; Imamah, Nur; Nuzula, Nila Firdausi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2023)
Businesses focused on sustainable growth would consider intangible assets with unique characteristics that are difficult to imitate in order to provide their business a competitive edge to be the most valuable productive assets. The purpose of this study is to examine the role that the company's intangible assets—specifically, its social and intellectual capital—have in improving overall performance. Manufacturing companies listed on the IDX between 2016 and 2020 make up the study's population. In order to address current hypotheses, the analytical procedure consists of testing the measurement model and structural model. The study's findings demonstrate that intellectual capital directly improves a company's success. But it hasn't been demonstrated that other intangible assets, including social capital, have a direct effect on the firm performance. The results of this model are expected to contribute in improving corporate governance and increasing stakeholder trust in company performance.